2020
DOI: 10.1002/jso.26358
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of all‐polyethylene and metal‐backed modular tibial components in endoprosthetic reconstruction of the distal femur

Abstract: Introduction All‐polyethylene (AP) tibial components have demonstrated equivalent or improved long‐term survivorship and reduced cost compared with metal‐backed (MB) components in primary total knee arthroplasty; however, there is a lack of data comparing these outcomes in the setting of an oncologic endoprosthetic reconstruction. Methods A total of 115 (88 AP:27 MB) patients undergoing cemented distal femur endoprosthetic reconstruction following oncologic resection were reviewed. Mean age was 40 years and 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Unlike the femoral component, tibial components are available in both metal and all-polyethylene, and fixation of the tibial component can be achieved in a variety of ways, including cemented, cementless, and hybrid fixation. Despite the increased utilization of DFR with APTs over time, previous studies have paid little attention to the outcomes of tibial components until recently[ 6 , 9 , 20 ]. Bukowski et al [ 20 ] showed that DFRs with APT have a significantly lower incidence of tibial revision at 10 years (1.1% vs 12.5%, HR = 0.18, P = 0.03) and no difference in infection-free survival ( P = 0.72) when compared to the traditional DFR with a metal backed tibia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the femoral component, tibial components are available in both metal and all-polyethylene, and fixation of the tibial component can be achieved in a variety of ways, including cemented, cementless, and hybrid fixation. Despite the increased utilization of DFR with APTs over time, previous studies have paid little attention to the outcomes of tibial components until recently[ 6 , 9 , 20 ]. Bukowski et al [ 20 ] showed that DFRs with APT have a significantly lower incidence of tibial revision at 10 years (1.1% vs 12.5%, HR = 0.18, P = 0.03) and no difference in infection-free survival ( P = 0.72) when compared to the traditional DFR with a metal backed tibia.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increased utilization of DFR with APTs over time, previous studies have paid little attention to the outcomes of tibial components until recently[ 6 , 9 , 20 ]. Bukowski et al [ 20 ] showed that DFRs with APT have a significantly lower incidence of tibial revision at 10 years (1.1% vs 12.5%, HR = 0.18, P = 0.03) and no difference in infection-free survival ( P = 0.72) when compared to the traditional DFR with a metal backed tibia.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Due to differences in tumor site, fixation technique, and type of prosthesis, the incidence of aseptic loosening varies widely among studies, ranging from 0 to 27.5%. 2 , 5 , 22 , 27 - 35 …”
Section: Prosthetic Survival Rate and Complicationsmentioning
confidence: 99%
“…27 Due to differences in tumor site, fixation technique, and type of prosthesis, the incidence of aseptic loosening varies widely among studies, ranging from 0 to 27.5%. 2,5,22,[27][28][29][30][31][32][33][34][35] Patients with aseptic loosening are often accompanied by increasing weight-bearing pain, and different degrees of displacement of the prosthesis and the formation of radiolucencies around prosthesis can be seen on the X-ray film. If the aseptic loosening is only visible in the imaging examination and the patient has no obvious symptoms of discomfort, clinician can choose not to intervene.…”
Section: Aseptic Looseningmentioning
confidence: 99%
“…Massive endoprostheses have become commonly used for bony reconstruction after oncologic resections of the lower limbs because of their off-the-shelf availability, modularity, and durability [1,5,[9][10][11]. In the United States, these implants are modular and made of cobalt-chromium and titanium alloys [12,20,21].…”
Section: Introductionmentioning
confidence: 99%